1995
DOI: 10.1128/aac.39.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Skin uptake, distribution, and elimination of antimony following administration of sodium stibogluconate to patients with cutaneous leishmaniasis

Abstract: We examined in this study the pharmacokinetics of Sb in the affected skin and normal skin of patients treated with sodium stibogluconate for cutaneous leishmaniasis and compared the results with those for the blood. The procedure was fully explained, and a written consent was obtained from each of nine patients. After a dose of sodium stibogluconate equivalent to 600 mg of Sb was administered intramuscularly, small skin biopsies were collected under local anesthesia at different time intervals from the circumf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
(13 reference statements)
2
19
0
1
Order By: Relevance
“…Pharmacokinetic parameters of Sb V in humans have been described previously [11,12] and are similar to those measured in hamsters in this study. A consistent finding was the appearance of a second peak in the plasma concentration at ca.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Pharmacokinetic parameters of Sb V in humans have been described previously [11,12] and are similar to those measured in hamsters in this study. A consistent finding was the appearance of a second peak in the plasma concentration at ca.…”
Section: Discussionmentioning
confidence: 91%
“…However, no reports were found to indicate whether active tubular secretion has a role in Sb V elimination. ALJaser et al [12] reported Sb V renal clearance in patients infected with CL to be 211.7 ± 19.3 mL/min, which shows possible involvement of active tubular secretion in addition to glomerular filtration. Accordingly, the significant increase in AUC and decrease in CL/F of Sb V following multiple dosing could be due to FLZ competition with Sb V renal excretion in hamsters infected with CL.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…30 In the Mediterranean basin, biochemical differences were observed between dermatotropic and viscerotropic isolates of L. infantum . 31 However, other studies in different Mediterranean countries 32,33 showed that this association was not absolute.…”
Section: Discussionmentioning
confidence: 99%
“…SSG consists of Sb conjugated with glucose. After administration to humans, the peak concentration of Sb in plasma is approximately 10 g/ml (ϳ82 M) (1,7,11). Though such a peak Sb concentration seems relatively low compared to the SSG EC 50 for HCV inhibition found in this study (0.2 to 0.3 mg/ml of SSG or 345 to 517 M of Sb), several factors should to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%